Audit and Taxation - Ashokan, Sharanya (ATLAS SkillTech University, 2024)
AJAY B GARG CHARTERED ACCOUNTANT is a well-established CA firm located in Mumbai, India, with a successful track record of 25 years in operation. Over the years, they have honed their expertise in navigating the competitive landscape, offering effective assistance through a skilled team of professionals and staff. This experience has uniquely positioned them to provide solutions for both straightforward and intricate commercial scenarios.
Project Report on Audit and Taxation (2022-24) Under the Guidance of Prof. Chetana Asbe
Keywords: CA; Accounting; Accountancy